2019
DOI: 10.3390/ijerph16122067
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Messages Associated with Low UV Index Values Need Reconsideration

Abstract: Overexposure to ultraviolet (UV) radiation is the main modifiable risk factor for skin cancer. The Global Solar Ultraviolet Index (UVI) was introduced as a tool to visualize the intensity of UV radiation on a certain day, which should enable and encourage people to take appropriate protective measures. The ‘low’ exposure category of the UVI, defined by a rounded UVI value of 0, 1 or 2, was linked to the health message ‘No protection required’ by the World Health Organization and partner organizations. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The World Health Organization and many other government and non-government organisations advise that sun protection is not required when the UV index is below 3. This advice has been challenged previously based on UV radiation data from New Zealand [ 124 ] and is supported by a new study from Germany [ 125 ]. Using data from nine ground-based monitoring stations from 2007 to 2016, Lehmann and colleagues found that when the UV index is 2, people with Fitzpatrick skin types I and II can receive a minimal erythemal dose of UV radiation in 1.5 h [ 125 ].…”
Section: Human Healthmentioning
confidence: 99%
“…The World Health Organization and many other government and non-government organisations advise that sun protection is not required when the UV index is below 3. This advice has been challenged previously based on UV radiation data from New Zealand [ 124 ] and is supported by a new study from Germany [ 125 ]. Using data from nine ground-based monitoring stations from 2007 to 2016, Lehmann and colleagues found that when the UV index is 2, people with Fitzpatrick skin types I and II can receive a minimal erythemal dose of UV radiation in 1.5 h [ 125 ].…”
Section: Human Healthmentioning
confidence: 99%
“…Therefor the unitless UVI, always given as an integer value, is divided into five categories: low (values 0-2), moderate (3-5), high (6-7), very high (8)(9)(10), and extreme (11+). A low value means that sun protection is only needed for individuals with very light skin during an extended outdoor stay [28]. Starting from moderate values, sun protection measures including sunscreen use (and re-application), sunglasses, protective clothing, and staying in the shade (especially around solar noon) are recommended [25].…”
Section: Introductionmentioning
confidence: 99%
“…(Supplementary Table 3) Despite overwhelming scrutiny, the UVI has been adopted by many governments as the standard platform for public communication of UV exposure risk since its inception by the WHO 1994 [37]. Many of the research efforts detailing UVI knowledge have shown there is a minimal understanding of the UVI by the public [51,54,[85][86][87][88][89][90] and that lower UVI value recommendations underpredict erythemal risk [91][92][93]. Medical professionals have similarly displayed limited knowledge or use of the UVI [94][95][96].…”
Section: Resultsmentioning
confidence: 99%